2018
DOI: 10.1186/s13287-017-0752-6
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stromal cell-derived exosome-rich fractionated secretome confers a hepatoprotective effect in liver injury

Abstract: BackgroundMesenchymal stromal cells (MSCs) are an attractive therapeutic agent in regenerative medicine. Recently, there has been a paradigm shift from differentiation of MSCs to their paracrine effects at the injury site. Several reports elucidate the role of trophic factors secreted by MSCs toward the repair of injured tissues. We hypothesize that fractionating the MSC secretome will enrich exosomes containing soluble bioactive molecules, improving its therapeutic potential for liver failure.MethodsRat bone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
91
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(109 citation statements)
references
References 60 publications
7
91
1
2
Order By: Relevance
“…Previous studies have demonstrated that co-transplantation of hepatocytes and MSCs exerted a signi cant therapeutic effect on ALF animal models, in which MSCs support hepatocellular metabolism and stabilization in ALF. (38) In the current study, in the co-capsulation system of UMSCs and hepatocytes, in vitro, UMSCs promoted the synthesis and secretion of human primary hepatocytes and enhanced the viability and function of hepatocytes ( Fig.1D-1E). In vivo, UMSC-HEP-APA reduced decreased mortality rate, hepatic apoptosis and necrotic level (Fig.2), inhibited in ammatory response including an alleviated neutrophil and macrophage in ltration in the liver, in ammatory factors levels (Fig.3).…”
Section: Discussionsupporting
confidence: 51%
“…Previous studies have demonstrated that co-transplantation of hepatocytes and MSCs exerted a signi cant therapeutic effect on ALF animal models, in which MSCs support hepatocellular metabolism and stabilization in ALF. (38) In the current study, in the co-capsulation system of UMSCs and hepatocytes, in vitro, UMSCs promoted the synthesis and secretion of human primary hepatocytes and enhanced the viability and function of hepatocytes ( Fig.1D-1E). In vivo, UMSC-HEP-APA reduced decreased mortality rate, hepatic apoptosis and necrotic level (Fig.2), inhibited in ammatory response including an alleviated neutrophil and macrophage in ltration in the liver, in ammatory factors levels (Fig.3).…”
Section: Discussionsupporting
confidence: 51%
“…The size and concentration of exosomes were analyzed by NanoTracking System Analysis using the NanoSight NS500 equipment (NanoSight Ltd, Amesbury, United Kingdom) and by transmission electron microscopy with a Phillips Morgagni electron microscope as previously reported (Damania et al . ). Gel electrophoresis and Western blots were performed to confirm the enrichment of exosome markers (GM130, ALIX, Flotilin and EpCAM) in exosome samples compared to whole cell lysate using the Exosomal Marker Ab sampler kit (Cell Signaling Technology, Danvers, MA).…”
Section: Methodsmentioning
confidence: 97%
“…Additional studies both in vitro and in vivo have shown the marked ability of MSC‐derived exosomes to reduce oxidative stress and cell damage in several pathological conditions including hydrogen peroxide incubation, carbon tetrachloride administration, acetaminophen tissue injury and ischemic cardiomyopathy (Damania et al . ; Shi et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…Intriguingly, Wu et al demonstrated that MSCderived exosomes promoted the conversion of hepatocytes into hepatic oval cells to promote liver regeneration [94]. Exosomes improve cell recovery and reduce cytotoxicity in APAP-and hydrogen peroxide-treated hepatocytes [95]. MSC-derived exosomes significantly inhibit APAPinduced apoptosis of hepatocytes via upregulation of Bcl-xL levels but not through modulation of oxidative stress in vitro [96].…”
Section: Msc Derivatives For Apap-induced Liver Injurymentioning
confidence: 99%